PENERAPAN MODEL PEMBELAJARAN SCIENCE, TECHNOLOGY, ENGINEERING, MATHEMATICS (STEM) TERHADAP KETERAMPILAN BERPIKIR KREATIF SISWA KELAS V - Setiawan, Yogi; Rohmah, Zulfiani Ainur (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This research is motivated by the low level of creative thinking skills among students in science and science learning and the infrequent use of innovative learning models such as Science, Technology, Engineering, and Mathematics (STEM). This study aims to determine the differences in creative thinking skills between students learning with the STEM model and those learning with conventional models. The method used was a quasi-experimental design with a non-equivalent control group design for 25 students in the experimental class and 28 students in the control class at SD Negeri Gandu I. The instrument was a descriptive test with indicators of fluency, flexibility, originality, and elaboration. The results showed that the average post-test score for the experimental class (82.40) was higher than the control class (71.18) with a significance level of <0.05, indicating a significant difference. The implementation of the STEM model not only increased the average score but also encouraged students to be more active, creative, and engaged in learning. This model can be an effective alternative for teachers in developing 21st-century skills. The implications of this research demonstrate the importance of project-based learning innovation in improving the quality of basic education. ABSTRAKPenelitian ini dilatarbelakangi oleh rendahnya keterampilan berpikir kreatif siswa pada pembelajaran IPAS dan jarangnya penggunaan model pembelajaran inovatif seperti Science, Technology, Engineering, Mathematics (STEM). Penelitian ini bertujuan mengetahui perbedaan keterampilan berpikir kreatif antara peserta didik yang belajar dengan model STEM dan siswa dengan model konvensional. Metode yang digunakan adalah kuasi eksperimen dengan desain non-equivalent control group pada 25 siswa kelas eksperimen dan 28 siswa kelas kontrol di SD Negeri Gandu I. Instrumen berupa tes uraian dengan indikator fluency, flexibility, originality, dan elaboration. Hasil menunjukkan rata-rata post-test kelas eksperimen (82,40) lebih tinggi dibandingkan kelas kontrol (71,18) dengan signifikansi < 0,05, yang berarti terdapat perbedaan signifikan. Penerapan model STEM tidak hanya meningkatkan nilai rata-rata, tetapi juga mendorong siswa lebih aktif, kreatif, dan terlibat dalam pembelajaran. Model ini dapat menjadi alternatif efektif bagi guru dalam mengembangkan keterampilan abad ke-21. Implikasi penelitian ini menunjukkan pentingnya inovasi pembelajaran berbasis proyek untuk meningkatkan kualitas pendidikan dasar.